Health-related quality of life of young academics: A cross-sectional survey of universities in Wuhan, China - Yao, Qiang; Yang, Fei; Li, Hanxuan; Tang, Kaiyue; Liu, Chaojie (Frontiers in Psychology, 2022)
Objective: This study aimed to assess the health-related quality of life (HRQoL) of young academics in Wuhan, China, and its determinants. Methods: A multistage stratified cluster sampling strategy was employed to recruit study participants (young academics <40 years old) from 12 universities in Wuhan. A total of 301 respondents returned a self-complete questionnaire that contained the EQ-5D-5L. Multivariate linear and Tobit regression models were established to determine the sociodemographic and job predictors of the visual analogue scale (VAS) score and the EQ-5D utility index, respectively. Results: The study participants reported a mean VAS value of 79.42 (SD=10.51) and a mean EQ-5D utility index of 0.915 (SD=0.090). Anxiety/depression was the most frequently reported problem (65.12%), followed by pain/discomfort (43.52%). Transitioning towards a full professorship in national key universities (p<0.001), lower income (p<0.05) and too much pressure for academic promotion (p<0.001) were significant predictors of lower HRQoL; whereas, maintaining routines in physical activities (p<0.001), sleep (p<0.001) and meals (p<0.001), a good relationship with colleagues and family members (p<0.001), and social activities (p<0.01) were significant predictors of higher HRQoL. Conclusions: Low HRQoL of young academics in China is evident, as indicated by the 7.08 and 0.049 gap in VAS and utility index, respectively, compared to the general population at the same age. Work and career pressures are associated with the low HRQoL of young academics. The findings of this study highlight the importance of work-life balance in promoting HRQoL of young academics in universities in China.